THU0374 GENDER DIFFERENCE IN ASAS HEALTH INDEX IN PATIENTS WITH ANKYLOSING SPONDYLITIS. (June 2019) - Chen, Hsin-Hua; Pan, Ting-I; Chen, Yi-Ming; Lai, Kuo-Lung; Hsieh, Tsu-Yi; Lin, Ching-Tsai; Hung, Wei-Ting; Chou, Yin-Yi; Tseng, Chih-Wei; Wu, Yi-Da; Hsieh, Chia-Wei; Huang, Wen-Nan; et al.
Abstract : Background: The Assessment of Spondyloarthritis international Society Health Index (ASAS HI) has been develop and validated to assess health and function in patients with spondyloarthritis. However, whether ASAS HI differs between men and women is unknown. The aim of this study was to compare ASAS HI between men ans women in patients with ankylosing spondylitis (AS). Objectives: The aim of this study was to compare ASAS HI between men ans women in patients with ankylosing spondylitis (AS). Methods: Since November 2016, we measured and recorded data of demography, comorbidity, family history, medication use, the Ankylosing Spondylitis Disease Activity Score (ASDAS), the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), the Bath Ankylosing Spondylitis Functional Index (BASFI), the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS) and the ASAS HI for AS patients in clinical practice using an electronic patient reported data system linked to an electronic medical record system in Taichung Veterans General hospital (TCVGH). We retrieved the last recorded data of AS patients in TCVGH during 2017/11–2018/10. We assessed the association between gender and the ASAS HI using a multivariable linear regression model. Variables from the univariable linear regression analysis with p < 0.2 were included in then multivariable analysis. We used a forward selection method to build the models. Results: A total of 307 AS patients [62 (20.2%) females, mean age 46.4 years (S.D. 13.3), mean symptom duration 20.6 years (S.D. 12.1)] were included. Female patients had an older age at onset (29.2 ± 12.6 vs 24.9 ± 9.6 years, p = 0.015), a shorter symptom duration (15.7 ± 11.6 vs 21.8 ± 12.0 years, p < 0.001), a lower proportion of smoking (6.5% vs 48.2%, p < 0.001), higher ASAS HI (5.9 ± 3.8 vs 4.3 ± 3.4, p = 0.001), higher ASDAS-ESR (1.9 ± 0.8 vs 1.5 ± 0.8, p < 0.001) and lower mSASSS (6.0 ± 11.4 vs 21.8 ± 23.1, p < 0.001) than male patients. There were no significant differences in BASFI (1.1 ± 1.6 vs. 1.2 ± 1.7, p = 0.765), ASDAS-CRP (1.5 ± 0.9 vs. 1.5 ± 0.9, p = 0.972) and BASDAI (2.4 ± 1.8 vs. 2.0 ± 1.4, p = 0.115) between females and males. In multivariable analysis, male gender was significantly associated with a better ASAS HI ( B = -1.73, 95% CI: -2.55, -0.91, p < 0.001). Other significant predictors of ASAS HI included BASDAI ( B = 1.29, 95% CI: 1.07, 1.50, p < 0.001), disease duration ( B = 0.04, 95% CI: 0.01, 0.06, p = 0.015), mSASSS ( B = 0.02, 95% CI: 0.01, 0.04, p = 0.003) and hepatitis B ( B = 0.99, 95% CI: 0.03, 1.96, p = 0.044). Conclusion: This single center, cross-sectional study revealed that male gender was significantly associated with lower ASAS HI in AS patients. Reference: [1] Kiltz U, van der Heijde D, Boonen A, Akkoc N, Bautista-Molano W, et al. 2018. Measurement properties of the ASAS Health Index: results of a global study in patients with axial and peripheral spondyloarthritis. Annals of the rheumatic diseases 77:1311-7. Disclosure of Interests: Hsin-Hua Chen Speakers bureau: Johnson & Johnson, Novartis, Pfizer, Abbvie, Roche, UCB, Bristol-Myers Squibb, Chugai, Ting-I Pan: None declared, Yi-Ming Chen Grant/research support from: GSK, Pfizer, BMS, Astra & Zeneca, Consultant for: Pfizer, Novartis, Abbvie, Johnson & Johnson, BMS, Roche, Sanofi, MSD, Guigai, Astellas Inova Diagnostics, UCB Agnitio Science Technology, United Biopharma, Thermo Fisher, Paid instructor for: Pfizer, Novartis, Abbvie, Johnson & Johnson, BMS, Roche, Astra& Zeneca, Sanofi, MSD, Guigai, Astellas UCB Thermo Fisher, Speakers bureau: Pfizer, Novartis, Abbvie, Johnson & Johnson, BMS, Roche, Lilly, GSK, Astra& Zeneca, Sanofi, MSD, Guigai, Astellas UCB Thermo Fisher, Kuo-Lung Lai: None declared, Tsu-Yi Hsieh: None declared, Ching-Tsai Lin: None declared, Wei-Ting Hung: None declared, Yin-Yi Chou: None declared, Chih-Wei Tseng: None declared, Yi-Da Wu: None declared, Chia-Wei Hsieh: None declared, Wen-Nan Huang: None declared, Yi-Hsing Chen: None declared, Der-Yuan Chen: None declared